2022
DOI: 10.3389/fpsyt.2022.860448
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Excitation/Inhibition Imbalance in Young Adults With Autism Spectrum Disorder: A MRS-TMS Approach

Abstract: Excitatory/inhibitory imbalance has been suggested as a neurobiological substrate of the cognitive symptomatology in Autism Spectrum Disorder (ASD). Studies using magnetic resonance spectroscopy (MRS) attempted to characterize GABA and Glutamate brain levels in ASD. However mixed findings have been reported. Here, we characterize both neurochemical and physiological aspects of GABA system in ASD by implementing a more comprehensive approach combining MRS and transcranial magnetic stimulation (TMS). A group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Green clustering includes Biological Psychiatry, Frontiers in Psychiatry, and Autism Research . These studies have mainly focused on the potential mechanisms of neuromodulation techniques in the treatment of autism [ 48 ]. Blue clustering includes Applied Psychophysiology and Biofeedback, The Journal of Autism and Developmental Disorders, and Autism .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Green clustering includes Biological Psychiatry, Frontiers in Psychiatry, and Autism Research . These studies have mainly focused on the potential mechanisms of neuromodulation techniques in the treatment of autism [ 48 ]. Blue clustering includes Applied Psychophysiology and Biofeedback, The Journal of Autism and Developmental Disorders, and Autism .…”
Section: Resultsmentioning
confidence: 99%
“…This may limit research progress on the treatment of ASD using neuromodulation techniques. The top 10 journals in terms of number of publications and citations were mainly involved in the fields of neuromodulation, neuroscience, and mental cognition, which showed that neuromodulation techniques have received extensive attention in neuropsychiatric disorders, especially in improving the psychological and cognitive impairment of patients with ASD [ 47 , 48 , 76 , 83 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, general data analysis for advanced MRS methods such as HERMES continue to evolve, including modeling the baseline and data fitting. The tissue correction methods carried out in this study include an α-correction to account for higher GABA in GM than WM as this method is widely used in studies examining GABA+ in the literature ( Ip et al, 2021 , Bernardino et al, 2022 , Heise et al, 2022 , Stoby et al, 2022 , Trujillo et al, 2022 ). Relative GM vs WM levels of other metabolites, such as GSH and Glu are not defined ( Srinivasan et al, 2010 , An et al, 2015 , Chan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%